Proceedings of the 2003 IEEE International Symposium on Intelligent Control ISIC-03 2003
DOI: 10.1109/isic.2003.1253914
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear disturbance rejection for magnetic levitation systems

Abstract: In this paper, a position regulation contml rtmtegy is developed for (L magnetic levitation system opemting in the presence of a bounded, nonlinear, periodic disturbance. The pmposed contmller utilizes a sotumted control fone input in conjunction k6th D learning based dbturbonce mtimntor to 's$"-totically regulate the target mom to D desimd set point position despite the oetuotor's unidirectional limitation of ezerting only an attmctiw fome on the target moss (i.e., the contml input a n only generate on ottmct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Both simulation and experiments indicated that the dynamic stiffness of their system was increased. Fang, Feemster and Dawson [2] reported a position regulation control strategy developed for a magnetic levitation system operating in the presence of a bounded, nonlinear, periodic disturbance. They included simulation results, but no experimental data was reported.…”
mentioning
confidence: 99%
“…Both simulation and experiments indicated that the dynamic stiffness of their system was increased. Fang, Feemster and Dawson [2] reported a position regulation control strategy developed for a magnetic levitation system operating in the presence of a bounded, nonlinear, periodic disturbance. They included simulation results, but no experimental data was reported.…”
mentioning
confidence: 99%